Longitudinal clinical course, treatment outcomes, and relapse patterns in alopecia areata: a prospective cohort study - Wenjie, Yan; Yue, Wang; Mengjiao, Wang; Yumei, Zhao; Xi, Huang (Frontiers in Medicine, 2025)
BackgroundAlopecia areata (AA) is a common autoimmune hair loss disorder with a highly variable course and substantial psychosocial impact. Evidence from long-term prospective cohorts remains limited. To characterize the natural history, treatment outcomes, relapse patterns, quality-of-life changes, and safety profile of AA over 52 weeks in a real-world clinical setting.MethodsIn this single-center prospective cohort, 400 patients with AA and 80 healthy controls were followed for 52 weeks, with assessments at weeks 4, 12, 24, 36, and 52. Disease severity was quantified using the Severity of Alopecia Tool (SALT). Primary outcomes included SALT50 and SALT90 achievement at week 24; secondary outcomes were relapse at week 52, patient-reported outcomes [Dermatology Life Quality Index (DLQI), Skindex-16, itch/pain numeric rating scale (NRS)], and safety. An imaging subcohort (n = 120) underwent dermoscopy and high-frequency ultrasound. Statistical analyses comprised mixed-effects models, logistic and Cox regression, ROC analyses, and correlation testing.ResultsBy week 52, 31.8% of patients relapsed, with a median relapse time of 28 weeks. SALT improved over time, with mean scores declining from 38.6 ± 21.7 at baseline to 22.4 ± 17.1 at week 52 (P < 0.001). At week 24, 62.5% achieved SALT50 and 28.3% achieved SALT90, with active disease, shorter duration, and younger age predicting better outcomes. ROC analysis showed improved discrimination for the enhanced model including activity and duration (AUC 0.81 vs. 0.69, P = 0.006). By week 52, 31.8% relapsed (median time 28 weeks), with relapse risk highest in those with prior episodes (HR 1.61, 95% CI 1.17–2.21). Quality-of-life indices improved significantly (DLQI −7.1, Skindex-16 −15.4 from baseline to week 52, both P < 0.001), and itch/pain reduction correlated with SALT improvement (r = 0.41 and 0.23, respectively). Dermoscopic and ultrasound parameters correlated with baseline severity and improved prediction of therapeutic response (AUC up to 0.84).ConclusionThis prospective cohort provides longitudinal evidence that baseline severity, disease activity, and relapse history are major determinants of response and recurrence in AA. Standardized severity scores, patient-reported outcomes, and imaging biomarkers may improve risk stratification, personalized care, and real-world evaluation of current therapies.